FAKTOR KESULITAN BELAJAR DAN MINAT BELAJAR PADA MATA PELAJARAN IPS TERHADAP HASIL BELAJAR SISWA DI SMPN 1 HINAI - Ayunda, Tasya; Siregar, Zulham (Prodi Pendidikan IPS STKIP AL MAKSUM, 2025)
Learning Difficulties Are A Condition In The Teaching Process Where Students Cannot Learn Optimally. This Study Has A Significant Purpose To Find Out How Much The Influence Of Difficulties On Social Studies Learning Materials At Smpn 1 Hinai In Influencing Student Learning Outcomes. The Purpose Of This Research Is Also To Find Out What Factors Cause Learning Difficulties In Students At Smpn 1 Hinai. This Research Is A Qualitative Research That Uses A Research Method Using A Descriptive Approach. The Results Of This Study Showed That Students At Smpn 1 Had Learning Difficulties Due To Several Factors, Including Internal Factors And Also External Factors. Internal Factors Are The Lack Of Motivation Given By Teachers And Parents And The Lack Of Interest Of Students In Participating In Social Studies Learning Activities Which Are Considered Boring Due To The Lack Of Tools And Props In Delivering The Material. Meanwhile, External Factors Are That Teachers Are Still A Little Confused In Delivering Learning Materials In Accordance With The Curriculum That Runs Due To The Lack Of Learning Books And Tools That Support The Learning Process. Therefore, The Role Of Teachers Is Very Influential In Supporting Students' Learning Interests And Overcoming Students' Learning Difficulties. Teachers Are Expected To Be Able To Convey Assignments In An Interesting Way To Arouse Students' Interest In Learning.